Parenting Lessons from Bringing Up Bébé: A Comparative Analysis with Islamic Education for Character Building - Zahro, Latifatuz; Sutiah, Sutiah (GENIUS: Indonesian Journal of Early Childhood Education, 2024)
This study examines the parenting principles from Pamela Druckerman’s Bringing Up Bébé within the framework of Islamic education, with a focus on character building in early childhood. By employing a qualitative and descriptive-analytic approach, the research compares key parenting practices such as discipline, self-control, independence, and communication, highlighting their alignment with Islamic values. The findings demonstrate significant parallels between French parenting techniques and Islamic teachings, particularly in fostering discipline and respect. By integrating these principles into Indonesian parenting practices, the study offers actionable insights for addressing contemporary parenting challenges while preserving Islamic values. This research underscores the universality of effective parenting methods and recommends further exploration of their applicability across diverse cultural and religious contexts.